Biofertilizantes, a base de esterco bovino, no controle de Phytophthora nicotianae em citros - Wehr, Pitt Paul (2014)
The objective of this study was to evaluate the effect of two organic liquid fertilizeres made from fresh cattle manure, produced under anaerobic digestion or forced oxygenation, for the control of Phytophthora nicotianae. Furthermore, we aimed to investigate separately the effect of the components in these products over the pathogen. For so, we tested the effect of cultivable microorganisms and the filtered fraction over the pathogen, targeting to identify the role of this factors in the disease control. It was found that biofertilizers have substances and microorganisms present in its composition capable of operating in the pathosystem in question, highlighting the role of baciliform heat resistant bacteria. It was observed that the effect of the filtered fraction of the anaerobic biofertilizer was effective on the mycelial growth of the pathogen and significantly higher than the filtered fraction of the aerobic biofertilizer, and had higher levels of some nutrients, especially calcium, copper and iron. The aerobic biofertilizer showed greater quantity and diversity of microorganisms antagonistic to P. nicotianae. The application of both biofertilizers reduced the number of infected roots of two citrus rootstocks (Citrus limonia and Citrus sunki) Both biofertilizers also reduced the amount of pathogen inoculum in the soil. In high concentrations biofertilizers cause phytotoxicity on young citrus plants, but in moderate concentrations, the products increased the number of germinated seeds of Rangpur lime and mandarin Sunki sown on soil inoculated with the pathogen. This makes the use of biofertilizers an option to be integrated in the disease management of P. nicotianae in citrus, however, more studies are require to investigate other issues, such as the risks related to the application of this products.